Can Additional Inoculations Increase Soybean Nodulation and Grain Yield?. (1st March 2018) - Moretti, Luiz Gustavo; Lazarini, Edson; Bossolani, João William; Parente, Tiago Lisboa; Caioni, Sheila; Araujo, Ricardo Silva; Hungria, Mariangela
Abstract : Core Ideas: A full set of N2 –fixing nodules can supply soybean N demands. Seed inoculation increased nodulation and grain yield of field‐grown soybean. Additional spray inoculations (V1, V3, V6, R1, or R3) resulted in further increases. New nodules and grain yield increases can be achieved by additional inoculations. Highly productive soybean [ Glycine max (L.) Merr.] genotypes require that large amounts of N be supplied throughout the growth cycle to attain high yields. The nutrient can be obtained through biological N2 fixation by elite bradyrhizobial strains if a set of fully functional nodules is available. This study was conducted during two crop seasons in the central‐west region of Brazil to investigate if additional inoculations via spray applications of bradyrhizobia at different stages of the growth cycle can result in increased nodulation and grain yield. Even though the soils had high populations of soybean bradyrhizobia, seed inoculation at sowing increased grain yield by 28 and 27% in the first and second seasons, respectively, compared to the non‐inoculated control. Additional inoculations performed until the R6 stage significantly increased soybean nodulation, which might indicate that plants were able to overcome the limitations of autoregulation of nodulation, allowing the development of new functional nodules to sustain the increased demand for N at latter stages of the growth cycle, especially during pod filling. In response to the increased nodulation, grain yield gains of 2 and 7% were obtained in the first and second experiments, respectively, relative to inoculation at sowing only. Our results indicate that soybean roots can form new nodules in response to additional inoculations, promoting increased N2 fixation and higher grain yield.